MEMORI KETAKUTAN ANAK SEBAGAI SUMBER INSPIRASI KARYA SENI PATUNG - Silviya Sukmawati; Effy Indratmo (Texture:Art and Culture Journal, 2021)
Violence from parents and violence from the immediate environment at the age of children causes them to become children who are easily afraid of sounds (Verbal), fear of physical violence (objects), and fear of the immediate environment. This final artwork project aims to create a sculpture art with the theme of the memory of a child's fear, which also explains the concept and process of creation and also the visual aesthetics of sculpture. The shape of the memory of children's fear is portrayed in the media of sculpture art with cast printing techniques. The creation of sculpture in this final project provides more insight into empirical experiences in creating works of art as well as the deepening of concepts in children's memory of fears.